Pengaruh Brand Awareness Terhadap Repurchase Intention Dengan Brand Loyalty Sebagai Variabel Mediasi (Studi Pada Konsumen Queen Apple di Kota Batu) - Regina Yusi Ananda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The study aims at identifying the direct and indirect effect of brand awareness and brand loyalty towards repurchase intention of customer Queen Apple in Kota Batu. The research type was explanatory research which explain about causal relation between variables from the research hypothesis. This study uses 140 respondents of Queen Apple consumers, selected using purposive sampling technique with the criteria of reaching 17 years of age at the minimum and having made at least one purchase in Queen Apple Kota Batu. The research instrument was assessed using validity, reliability, and classical assumption test. The hypothesis was evaluated using t-test in SPSS 23, and the data are carefully examined using path analysis. The results showed that brand awareness gives a significant effect on brand loyalty. Brand loyalty gives a significant effect on repurchase intention. Otherwise, brand awareness gives a significant effect on repurchase intention. Brand awareness had indirect influence towards repurchase intention through brand loyalty significantly.Keywords: Brand awareness, Brand loyalty, Repurchase Intention.